Digital trade coin: towards a more stable digital currency. Issue 7 (18th July 2018) - Lipton, Alex; Hardjono, Thomas; Pentland, Alex
Abstract : We study the evolution of ideas related to creation of asset-backed currencies over the last 200 years and argue that recent developments related to distributed ledger technologies and blockchains give asset-backed currencies a new lease of life. We propose a practical mechanism combining novel technological breakthroughs with well-established hedging techniques for building an asset-backed transactional oriented cryptocurrency, which we call the digital trade coin (DTC). We show that in its mature state, the DTC can serve as a much-needed counterpoint to fiat reserve currencies of today.